2020
DOI: 10.3389/fmed.2019.00303
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Iron Status and Risk of Chronic Kidney Disease in Chinese Adults

Abstract: Background: Even though it is well-known that iron deficiency is the result of chronic kidney disease (CKD), whether iron will affect kidney function and disease in the general population is not clear. We thus conducted a nationwide cross-sectional study using data from the China Health and Nutrition Survey (CHNS) to assess the relationship of iron status with estimated glomerular filtration rate (eGFR) and CKD among general adults. Methods: A total of 8,339 adults from the China Health and Nutrition Survey in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In addition, sTfR was elevated in chronic hypoxic diseases such as cystic fibrosis in a clinical study 8 . Second, there is a relationship between TfR and chronic diseases such as DM 9 , CKD 10 , heart failure 11 , and cancer 30 , 31 . In our study, high sTfR was associated with CKD.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, sTfR was elevated in chronic hypoxic diseases such as cystic fibrosis in a clinical study 8 . Second, there is a relationship between TfR and chronic diseases such as DM 9 , CKD 10 , heart failure 11 , and cancer 30 , 31 . In our study, high sTfR was associated with CKD.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have demonstrated a significant association between sTfR and chronic disease 9 , 10 . One longitudinal study showed that higher sTfR was associated with the risk of diabetes mellitus (DM) among overweight and obese participants 9 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed that the highest iron intake levels (<7 mg/day; ≥13.3 mg/day) were associated with an increased risk of CKD stage 3B and over compared with the intake at recommended levels (7–10 mg/day). CKD patients are recommended to consume adequate levels of iron to prevent anemia [ 21 ]. For the general population, there were few studies on the association between dietary iron intake and risk of CKD in prospective cohort study.…”
Section: Discussionmentioning
confidence: 99%
“…The factors consistently associated with ferritin levels both pretherapy in CHC patients and at 24 weeks posttherapy in SVR patients, such as ALT, TG, eGFR, and Fe/TIBC, exhibited fundamental links with ferritin, regardless of HCV infection. For example, ferritin levels > 1.5 times higher than normal are usually seen in patients with a > 6 month history of elevated ALT 25 , high TG levels are strongly associated with ferritin levels 26 , every 100 μg/L increase in 27 , and the positive association between ferritin levels and transferrin saturation (Fe/TIBC) reflects the correlation between iron store and iron availability 28 . In contrast, the pretherapy-only factors (sex, HOMA-IR, hemoglobulin and IFNL3-rs12979860 genotype) and posttherapy-only factors (TC and anti-HCV therapy) suggested potential links, direct or indirect, between HCV infection and ferritin levels.…”
Section: Discussionmentioning
confidence: 99%